The use of the CAD/CAM system in the previous aesthetic resolution of a patient with different substrates (Research, Society and Development, 2021)
Currently in dentistry, there are treatments that combine not only aesthetics and longevity, but also ease of execution and consequently saving time. The objective of this work is to demonstrate, through a clinical case report, the ability of the CAD/CAM CEREC (Ceramic Reconstruction) system to mimic the dental structure and standardize the dental substrate in the final result. The present study reports the preparation of previous restorations (13, 12, 11, 21, 22 and 23) in lithium disilicate (e.max - Ivoclar vivadent), in a female patient, 50 years old, with different dental substrates, through complete office systems (chair side). As results obtained: clinical steps successfully achieved, excellent adaptations of the pieces, mimicment of the dental structures, results in ceramic restorations of excellence, well indicated, qualified and aesthetically pleasing, which was the main reason why the patient attended.